HUBUNGAN KEMERUAPAN ANTARA PEMBOLEHUBAH MAKROEKONOMI, PASARAN SAHAM ISLAM DAN KONVESIONAL DI MALAYSIA - Mohd Hussin, Mohd Yahya (Jurnal Syariah, 2019)
This paper attemps to investigate the relationship between conditional Malaysian stock market volitility and conditional macroeconomic volatility using monthly data for Malaysia from January 1992 to May 2002. Conditional volatility is measured as Generalized Autoregressive Conditional Heteroscedasticity (GARCH) estimation. It employs monthly data including convesional stock market returns (KLCI), Islamic stock market returns (RHB) , money supply (M1) , exchange rates (MYR) , consumer pricing index (CPI) and industrial production index (IP) . The results indicate that KLCI is more volatile than RHB whereby volatility in macroeconomic variables just can explain volatility in KLCI stock market around 33% and for RHB stock market around 25%. However, only exchange rates variable (MYR) can predict the volatility in Malaysian stock market. To conclude, only 25% to 33% of the volatility in Malaysian stock market are explained by the volatility of macroeconomic variables. The rest is due to speculative activities.